Afatinib in Non‐Small Cell Lung Cancer Harboring Uncommon EGFR Mutations Pretreated With Reversible EGFR Inhibitors. (9th September 2015) - Heigener, David F.; Schumann, Christian; Sebastian, Martin; Sadjadian, Parvis; Stehle, Ingo; Märten, Angela; Lüers, Anne; Griesinger, Frank; Scheffler, Matthias; ,
Abstract : Background: Afatinib, an irreversible ErbB family blocker, is approved for treatment of patients with previously untreated non‐small cell lung cancer (NSCLC) harboring activating epidermal growth factor receptor ( EGFR ) mutations. Efficacy of afatinib in EGFR tyrosine kinase inhibitor‐naïve (TKI‐naïve) patients with uncommon EGFR mutations (other than exon 19 deletions or exon 21 point mutations) has been reported; however, efficacy in TKI‐pretreated patients with uncommon EGFR mutations is unknown. Materials and Methods: In the afatinib compassionate use program (CUP), patients with advanced or metastatic, histologically confirmed NSCLC progressing after at least one line of chemotherapy and one line of EGFR‐TKI treatment were enrolled. Demographic data, mutation type, response rates, time to treatment failure (TTF), and safety in patients harboring uncommon EGFR mutations were reported. Results: In 60 patients (63% female, median age 63 years [range: 30–84 years]), a total of 66 uncommon EGFR mutations including 30 T790M mutations were reported (18.4% and 11%, respectively, of known EGFR mutations within the CUP). Most patients (67%) received afatinib as third‐ or fourth‐line treatment. Median TTF was 3.8 months (range: 0.2 to >24.6 months; p = .244) in patients with uncommon mutations compared with 5.1 months (range: 0.1 to >21.1 months) in patients with common mutations ( n = 165). Pronounced activity was observed with E709X mutations (TTF >12 months). No new safety signals were detected. Conclusion: Afatinib is clinically active and well tolerated in many TKI‐pretreated NSCLC patients harboring uncommon EGFR mutations. Compared with results reported in TKI‐naïve patients, activity was also indicated in patients with T790M and exon 20 insertion mutations. Implications for Practice: This analysis consists of a large database of non‐small cell lung cancer patients with uncommon EGFR mutations who were previously treated with reversible EGFR tyrosine kinase inhibitors. Although indirectly assessed, the results indicate that patients with uncommon EGFR mutations can derive benefit from treatment with the irreversible ErbB family blocker afatinib, even in some cases of tumors harboring resistance‐mediating exon 20 mutations. In this study, adverse events were modest and consistent with previous reports on afatinib. Abstract : No standard treatment currently exists for non‐small cell lung cancer patients with rare EGFR mutations. First‐generation EGFR tyrosine kinase inhibitors (TKIs) have shown limited efficacy in these patients. In this study, afatinib demonstrated efficacy and was well tolerated. The findings indicate that afatinib may be a treatment option for some patients with rare EGFR mutations who progress on reversible EGFR TKIs.